Haematological Response of the African Catfish, Clarias Gariepinus (Clariidae) Exposed to Manganese - E.A.A, Olojo; G., Ladeji (Asian Journal of Biological and Life Sciences, 2012)
African catfish, Clarias gariepinus were exposed to two sub-lethal concentrations of manganese (T =6.48mg/l and T = 8.64mg/l) for 144-hours and 12 the blood samples were collected at 24h intervals to determine the effects of the exposure on the haematological parameters. Packed cell volume (PCV), haematocrit (Hb), red blood corpuscles (RBC) and white blood cell (WBC) values increased significantly while erythrocyte sedimentation rate (ESR) and lymphocyte count showed a drastic decline compared with the control. The short-term manganese exposure had no significant effect on mean cell volume (MCV), mean cell haematocrit (MCH), mean cell haemoglobin concentration (MCHC), and Neutrophil values. There was no significant difference in the blood response in the two concentrations. The study showed that short-term exposure of Clarias gariepinus to sub-lethal concentrations of manganese caused haematological changes.